2015
DOI: 10.1001/jamapsychiatry.2015.1131
|View full text |Cite
|
Sign up to set email alerts
|

Early Cannabis Use, Polygenic Risk Score for Schizophrenia and Brain Maturation in Adolescence

Abstract: assisted with recruitment and testing of the participants, technical assistance, and coordination of the imaging project in the ALSPAC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
110
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 156 publications
(126 citation statements)
references
References 60 publications
8
110
0
6
Order By: Relevance
“…A clear benefit of this approach is that, unlike smaller single studies designed to explicitly address a single research question, such broad spectrum studies allow for the accumulation of a large well-powered dataset that can be used to address multiple different research questions, including expected small effects of common genetic variation. Further, because many other studies use similar methodology (e.g., HCP; (Barch et al, 2013); Brain Genomics Superstruct Project; (Holmes et al, In press); IMAGEN; (French et al, 2015), results can be readily integrated into prior literature with an increased likelihood that additional data may become available for replication attempts. However, alongside these clear benefits, there are also limitations that must be considered.…”
Section: 0 Discussionmentioning
confidence: 99%
“…A clear benefit of this approach is that, unlike smaller single studies designed to explicitly address a single research question, such broad spectrum studies allow for the accumulation of a large well-powered dataset that can be used to address multiple different research questions, including expected small effects of common genetic variation. Further, because many other studies use similar methodology (e.g., HCP; (Barch et al, 2013); Brain Genomics Superstruct Project; (Holmes et al, In press); IMAGEN; (French et al, 2015), results can be readily integrated into prior literature with an increased likelihood that additional data may become available for replication attempts. However, alongside these clear benefits, there are also limitations that must be considered.…”
Section: 0 Discussionmentioning
confidence: 99%
“…Two other MRI studies have reported that cannabis users had smaller hippocampal volumes than non-users, but that this was not evident in cannabis users with hair samples that were positive for CBD 40,41 . However, the extent to which cannabis use is associated with neuroanatomical changes remains controversial: studies that have matched participants on alcohol use, or have accounted for heritable and genetic risk, have failed to find an association between cannabis use and brain structure [42][43][44] .…”
Section: Psychosismentioning
confidence: 99%
“…This mapping principle has been used to bring gene-expression data contained in the Allen Brain Atlas into a FreeSurfer-based anatomical parcellation of the cerebral cortex 155 . This allowed us, for example, to show that regional differences in cortical thickness associated with early cannabis use follow a regional gradient in the expression of CNR1 156 . Box 3: developmental structural neuroimaging Our first major longitudinal insight into the dynamics of in vivo human brain development came from a structural neuroimaging study 157 , which revealed that the maturational trajectory of human gray matter volume follows a curvilinear "inverted-U", rather than showing a linear progression to adult values.…”
Section: Box 2: Population Neurosciencementioning
confidence: 99%